The First Autopsy Case of Fatal Acute Cardiac Failure after Administration of Carfilzomib in a Patient with Multiple Myeloma - Teruhito Takakuwa; Ippei Otomaru; Taku Araki; Akiko Miura; Yotaro Fujitani; Yasuhide Mochizuki; Yoshimi Miyagi; Hideto Senzaki; Ryosuke Yamamura (Case Reports in Hematology)
Carfilzomib (CFZ) improves progression-free survival for patients with relapsed or refractory multiple myeloma (MM) but has shown higher frequency of cardiovascular adverse events (CVAEs) than other proteasome inhibitors. We report the first autopsy case of acute death from cardiac failure shortly after administration of carfilzomib. A 74-year-old female was diagnosed with IgA MM after a 2-year period of smoldering MM. She was refractory to both bortezomib plus dexamethasone and lenalidomide plus dexamethasone therapies, so she subsequently received CFZ in combination with lenalidomide and dexamethasone. The day after the start of the therapy, she complained of severe dyspnea with a significant decline in left ventricular ejection fraction. Her acute cardiac failure rapidly progressed, and she died on day 7 of the start of CFZ. The autopsy showed invasion of inflammatory cells between the myocardial cells and very little myocardial necrosis. There was no obvious thrombus in the coronary artery of the heart, and no infarction or amyloid deposition was observed in the myocardium. Pathological findings of hypersensitivity myocarditis, a drug-induced cardiomyopathy, appeared to agree with this case except for absence of an eosinophilic infiltration of the myocardium. A CFZ-induced CVAE is generally considered reversible. However, rapidly progressing fatal heart failure like in our case is rare. To characterize CFZ-associated CVAE, further case collection is needed.